2005
DOI: 10.1097/01.smj.0000168129.02664.79
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive Epidemiology of Infant Ingestion Calls to a Regional Poison Control Center

Abstract: Therapeutic misadventures caused by dosing errors in infants younger than 6 months of age were prevalent. Most errors occurred with inaccurate measurement of the medication, repeated dosing by caregivers, incorrect dosing interval, and incorrect route. Healthcare providers could increase prevention of therapeutic misadventures by educating caregivers on proper administration of medications and by demonstrating the use of appropriate measuring devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Common causes of 10-fold dosing errors include failure to place a leading zero before a decimal point (e.g., .3 mL), including a zero after a decimal point (e.g., 3.0 mL), and use of trailing zeros (e.g., 0.250 mg). 6,7,14 This study did not identify whether the error occurred in the prescribing, dispensing, or administration stage. Confused units of measure and dose or dispensing cup error were the other most common therapeuticerror scenarios coded in the study.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Common causes of 10-fold dosing errors include failure to place a leading zero before a decimal point (e.g., .3 mL), including a zero after a decimal point (e.g., 3.0 mL), and use of trailing zeros (e.g., 0.250 mg). 6,7,14 This study did not identify whether the error occurred in the prescribing, dispensing, or administration stage. Confused units of measure and dose or dispensing cup error were the other most common therapeuticerror scenarios coded in the study.…”
Section: Discussionmentioning
confidence: 94%
“…In 2005, Coco et al 6 reported that 53% of calls to a single poison control center involving infants six months of age or younger involved medication errors. Incorrect dose was the most common reason for the error, and the most common substances involved were ranitidine, metoclopramide, acetaminophen, and an infant cough and cold preparation.…”
Section: Discussionmentioning
confidence: 98%
“…Of these, 28% were due to an "incorrect dose" or quantitative dosing error. 11 Unfortunately, that study was limited by use of a convenience sample, a small number of cases (n = 358), and data from only a single poison control center (PCC).…”
mentioning
confidence: 99%
“…Despite the large number of paediatric poisonings worldwide, only a small minority of these children experience significant morbidity and mortality . Supportive management is sufficient for the majority of patients . In paediatric poisoning, which often presents with inaccurate patient history, early risk assessment errs on the cautious side and might explain the eventual low complication rate in this cohort.…”
Section: Discussionmentioning
confidence: 99%
“…7,10,[14][15][16][18][19][20][21][22] Supportive management is sufficient for the majority of patients. 15,16,18,22,27,[34][35][36] In paediatric poisoning, which often presents with inaccurate patient history, early risk assessment errs on the cautious side and might explain the eventual low complication rate in this cohort. Nearly half of transported patients in our study received only non-invasive monitoring or supportive care, which could be given by appropriately trained general transport providers.…”
Section: Discussionmentioning
confidence: 99%